RECYCLE: DARI SAMPAH MENJADI BUNYI (KAJIAN PENCIPTAAN MUSIK KELOMPOK WAYANG SAMPAH DI SURAKARTA) - Setyawan, Dony (Institut Seni Indonesia (ISI) Surakarta, 2019)
The Wayang Sampah (‘trash puppet’) group gives a new breakthrough inthe world of music and puppetry, as the sound phenomena that emergefrom musical instruments made from waste raw material, as well as theorganological and visual engineering of the waste become interestingreasons to study. The community’s inclination towards environmental issues becomes the main characteristic of the Wayang Sampah. The breakthrougho+ered is that the music must be sounded and that it must contain an environmental message for the public. For such cause, in their shows, theWayang Sampah always carry a message to save the environment from thedangers of poorly managed garbage. Second, the music used to accompanythe Wayang Sampah performance contains a composition that supports popmusic and tradition. Music is not always about the quality of sound and theconcept of music, but the breakthrough of medium sound is also animportant aspect in the world of music debate. The creativity of Toni Kondein manipulating the organology of waste or used goods is a breakthrough inthe world of recycling. Waste can create artistic sound with good musicalorganology engineering system. Third, this achievement in soundengineering leads to the compository process for new musical garaps. Themusical works presented in Wayang Sampah are works by Wahyu Tuwek.In their performance, Sojazz musicians perform musical interactions amongthe musicians in two forms of process. Gesture interactions include eyecontact, hand code, head jerking, lip reading and overall body postureapplied as cues while improvising. The second form of the process isthrough the musical interaction itself such as accompaniment, melodicphrase and rhythmic motif, tension growth, and trade four. The process ofmusical interaction applied by Sojazz musicians as mentioned above isthrough gesture used to create mutual interaction between musicians.Keywords: Recycle Music, Wayang Sampah, trash puppet.